Decision Making with Multi Criteria through Hierarchic Analysis Technique and its Effect on Customer Decision Procedure - Shahraki, Alireza; Zarea, Hadi; ., Abbas Jannesari (Information Management and Business Review, 2012)
Today, world competition situation is in a way that organizations need to increase the quality and increase the customer satisfaction, increase the benefit and decrease in outgoings, all at the sometime together. One side, goods prices increase and sever competition in market between goods, and on the other side, complexity in customers attitude and their vary expectations made disaster in management and share increase of the market. So, increase of effects on customer decision procedure as a new attitude in these situations born. Customer decision procedure is a kind of decision- making that is mode by the users. In general, decision-making is recognition processes through selection among different choices. How many criteria are used to analysis by the users? In addition, what kind of criteria do they consider? In addition, to what extent do they emphasize according to their favorites or goods importance. Hierarchic analysis procedure (AHP) is a decision-making with multi criteria that is suitable complex decisions, and consist of decision elements compare in where recognition of quality has encountered with problem. Ranking in decision choices of AHP is to solve the puzzle complexity AHP procedure by finding the specification through different choices, declare good buying decision.